2016
DOI: 10.1186/s13643-016-0294-5
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone vs. synthetic progestins and the risk of breast cancer: a systematic review and meta-analysis

Abstract: BackgroundUse of menopausal hormonal therapy (MHT)-containing estrogen and a synthetic progestin is associated with an increased risk of breast cancer. It is unclear if progesterone in combination with estrogen carries a lower risk of breast cancer. Limited data suggest differences between progesterone and progestins on cardiovascular risk factors, including cholesterol and glucose metabolism. Whether this translates to differences in cardiovascular outcomes is uncertain. We conducted a systematic review and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
55
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 23 publications
0
55
0
4
Order By: Relevance
“…There is ongoing search for new compounds able to control excessive endometrial stimulation from the estrogen component but without stimulatory effects on the breast. Lower doses of conventional progestogens, intra-uterine and other non-oral administrations [8,11], as well as the native progesterone hormone itself [26], have been suggested as candidates for safe combinations with estrogen. The combination of estrogen with a selective estrogen receptor modulator (SERM) is an alternative which seems to avoid stimulation of the breast [27].…”
Section: Discussionmentioning
confidence: 99%
“…There is ongoing search for new compounds able to control excessive endometrial stimulation from the estrogen component but without stimulatory effects on the breast. Lower doses of conventional progestogens, intra-uterine and other non-oral administrations [8,11], as well as the native progesterone hormone itself [26], have been suggested as candidates for safe combinations with estrogen. The combination of estrogen with a selective estrogen receptor modulator (SERM) is an alternative which seems to avoid stimulation of the breast [27].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, EPIC is easily the largest cohort study of MHT containing mP4 yet performed and in combination with the Asi et al . meta‐analysis would suggest that MHT regimens containing mP4 are associated with a significantly lower risk of breast cancer than those containing progestins.…”
Section: Discussionmentioning
confidence: 99%
“…Only three useful studies were found examining breast cancer risk; nevertheless, they do supply some compelling data. The E3N‐EPIC Study is a French prospective cohort study investigating cancer risk factors in nearly 100 000 women born between 1925 and 1950 …”
Section: Micronised Progesterone and Breast Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…В мета-анализе N. Asi и соавторов [20] было показано, что прогестерон связан с меньшим риском РМЖ по сравнению с синтетическими прогестинами в сочетании с эстрогеном (RR = 0,67, 95% ДИ 0,55-0,81, I 2 = 42%, p < 0,0001) 1 , однако ка-чество доказательств было низким из-за наблюдательной природы исследования. Для исключения женщин в пост-менопаузе, получавших синтетические прогестины, отлич-ные от МПА, проводился анализ чувствительности.…”
unclassified